Предмет: Геометрия,
автор: efanovadashuta
упростите выражения:
sin²a-1=
cos²a-1=
(1+sin a)(1-sin a)=
(cos a-1)(1+cos a)=
Ответы
Автор ответа:
0
sin²a-1=-(1-sin²a)=-cos²a
cos²a-1=-(1-соs²a)=-sin²a
(1+sin a)(1-sin a)=1-sin²a=cos²a
(cos a-1)(1+cos a)=cos²a-1=-(1-соs²a)=-sin²a
cos²a-1=-(1-соs²a)=-sin²a
(1+sin a)(1-sin a)=1-sin²a=cos²a
(cos a-1)(1+cos a)=cos²a-1=-(1-соs²a)=-sin²a
Автор ответа:
0
сos^2a-sin^2+1=2сos^2a-
Автор ответа:
0
1-sin2a/cos2a-1
Похожие вопросы
Предмет: Математика,
автор: arivikbagdasarova77
Предмет: Другие предметы,
автор: Tidj
Предмет: Английский язык,
автор: Аноним
Предмет: Информатика,
автор: cccccx
Предмет: Алгебра,
автор: Аноним